Integrasi Sistem Pesantren Berbasis Mahasiswa di STAI Miftahul Ula Kertosono Nganjuk - Yuli Choirul Umah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Abstract: The existence of Islamic boarding school until now could not be separated from the role of the community in maintaining, preserving and developing the quality of human resources. Concomitant with the development of science and technology, to face the global competition is needed the qualified of human resources and immoral. Based on this background, the focus of the problem which is to be studied in this research are: (1) How does the concept of schools and students at STAI Miftahul 'Ula Kertosono Nganjuk? (2) How is the integration of Islamic boarding schools based on students at STAI Miftahul 'Ula Kertosono Nganjuk? This study aimed to students and the academic community at STAI Miftahul 'Ula Kertosono Nganjuk. The approach used is qualitative descriptive. While the data collection method using techniques of observation, interviews, documentation, and questionnaire.The results showed: (1) Learning system in pesantren using sorogan and bandongan methods. The requirement in establish pesantren that must exist are: Kyai, cottage/boarders, students, mosque/mushalla and teaching to read Yellow Book (Kitab Kuning). While the student functions, namely: iron stock, agent of change, social control, moral force. And many more student involvement in various fields. (2) Integration of Islamic boarding schools based on students at STAI Miftahul 'Ula Kertosono Nganjuk using integration model of complementation, comparison and verification.Keywords: Integration, Islamic Boarding School, Students, Students’ Islamic Boarding School